Taxonomy of e-courses as instructional desiners tool - Leszek Rudak (Center for Open and Multimedia Eduacation of the University of Warsaw, 2010)
Three attributes of online courses were described in the article: the communication, the access and the organization, which values characterize every course. All acceptable values of these parameters where outlined as well as a usefulness of this taxonomy for instructional designers. A multi-stage procedure for designing e-courses is proposed and thoroughly discussed. It is reasonably sophisticated to be effective and simple enough to be actually implemented. Main steps of the procedure starting with educational goals and ending up with an e-course scheme construction are elaborated.